Exponential stabilization of an Euler-Bernoulli beam under boundary control - Lekdim, Billal (Journal of Innovative Applied Mathematics and Computational Sciences, 2023)
We study the free vibration of an Euler-Bernoulli beam without internal damping. By applying suitable control at the free boundary, we can exponentially dampen these vibrations. The exponential stability was proven using the Lyapunov method, and the results were confirmed through numerical simulation.